Wandering Distal End of Ventriculo-Peritoneal Shunt: Our Experience with Five Cases and Review of Literature - Kundal, Vijay Kumar; Gajdhar, Mufique; Sharma, Chetan; Agrawal, Deepak; Kundal, Raksha (Journal of Nepal Paediatric Society, 2013)
Ventriculo-peritoneal (VP) shunt is the most commonly performed procedure for the management of hydrocephalus. Although shunts have improved the morbidity and mortality associated with disordered Cerebrospinal fluid (CSF) mechanics over the past 30 years, they still are associated with many potentially avoidable complications in clinical practice. However, extrusion of VP shunt catheter is an unusual complication of VP shunt Surgery. We are presenting this unusual complication in five patients. The lower end of the shunt was seen extruding from anal opening in one patient, umbilicus in one, urethra in one, inguinal hernia sac in one and oral cavity in one patient. All of these patients were managed by shunt removal, intra venous antibiotics followed by shunt replacement on the other side except the patient with inguinal hernia sac. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6935 J. Nepal Paediatr. SocVol.32(3) 2012 266-269